The association between helicobacter pylori infection and Triglyceride-Glucose (TyG) index in US adults: A retrospective cross-sectional study - Wei Fu; Junlong Zhao; GuoBin Chen; Linya Lyu; Yao Ding; Liang-Bi Xu (PLoS ONE, 2025)
Background The Triglyceride-glucose (TyG) index is a marker for insulin resistance and metabolic syndrome, while Helicobacter pylori is linked to gastrointestinal diseases and may affect metabolic risks. This study examined the association between the TyG index and H. pylori infection in adults. Methods Data from 3797 participants in the NHANES 1999–2000 cycle were analyzed. The relationship between the TyG index and H. pylori infection was assessed using multivariate logistic regression and a two-piecewise logistic model to explore non-linear effects. Subgroup analyses were conducted based on age, sex, glucose levels, BMI, and CKD. Results A linear association between the TyG index and H. pylori infection was found. Subgroup analyses revealed significant interactions with a few variables. Conclusions This study indicates a linear relationship between the TyG index and H. pylori infection, suggesting metabolic influences on H. pylori infection and potential for targeted interventions in at-risk groups.